Peningkatan Keterampilan Menulis Teks Eksplanasi Menggunakan Model Cooperative Tipe Think Talk Write di Kelas V SDN 12 Padang Besi Kota Padang - Lusi Herlina Fitri; Ari Suriani; Elfia Sukma; Habibi (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This research is motivated by the low skills of writing explanatory texts of fifth-grade students of SDN 12 Padang Besi caused by difficulties in developing ideas and teacher-centered learning. This study aims to improve explanatory text writing skills through the implementation of the Think Talk Write cooperative learning model. The type of research used is Classroom Action Research with qualitative and quantitative approaches carried out in two cycles through the stages of planning, implementation, observation, and reflection. The research subjects consisted of a teacher and 19 fifth-grade students of SDN 12 Padang Besi. Data were collected through observation, tests, and documentation with instruments in the form of RPPM observation sheets, teacher and student activity sheets, and an assessment rubric for explanatory text writing skills. Qualitative data were analyzed descriptively to describe the learning process, while quantitative data were analyzed using percentages to determine the improvement in learning outcomes. The results of the study showed an improvement in the quality of learning planning, teacher and student activities, and explanatory text writing skills. Thus, the application of the Think Talk Write model has proven effective in improving the explanatory text writing skills of fifth-grade students of SDN 12 Padang Besi, Padang City.